1998
DOI: 10.1007/s003830050307
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pyloromyotomy: a safer technique

Abstract: A modified technique of laparoscopic pyloromyotomy was used to treat infantile hypertrophic pyloric stenosis. Introducing a 5-mm periumbilical port for visualization, two stab wounds are made on either side laterally to directly insert 2.7-mm instruments for manipulation. From the left, the stomach is grasped - not the duodenum! From the right, an inexpensive disposable arthroscopy knife is used to incise the serosa and begin the myotomy, which is completed with a laparoscopic spreader until the muscle is sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 6 publications
1
30
1
Order By: Relevance
“…There is no doubt that the laparoscopic approach requires more equipment and is technically more demanding, but it is not certain whether the longer operating time is detrimental to the young infant. A number of groups have reported similar operating times with both approaches 5,6,10,11 , whereas others have noted a shorter duration of operation with the laparoscopic procedure 9,16 . With increasing experience the operating time for laparoscopic pyloromyotomy might be expected to shorten and approach that achievable with the open procedure.…”
Section: Discussionmentioning
confidence: 95%
“…There is no doubt that the laparoscopic approach requires more equipment and is technically more demanding, but it is not certain whether the longer operating time is detrimental to the young infant. A number of groups have reported similar operating times with both approaches 5,6,10,11 , whereas others have noted a shorter duration of operation with the laparoscopic procedure 9,16 . With increasing experience the operating time for laparoscopic pyloromyotomy might be expected to shorten and approach that achievable with the open procedure.…”
Section: Discussionmentioning
confidence: 95%
“…All the reported laparoscopic techniques involve either grasping the duodenum or the stomach using a laparoscopic grasper for pyloric stabilization [6]. However, it is a common experience that laparoscopic pyloric stabilization is limited due to the small size of the grasper usually used.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a number a studies have shown that the standard laparoscopic pyloromyotomy is safe as the traditional operation through abdominal incision [3][4][5][6][7][8][9]. However, in comparing laparoscopic pyloromyotomy with circumumbilical technique, the cosmetic result of endoscopic approach may not be superior [10].…”
Section: Discussionmentioning
confidence: 99%